2012
DOI: 10.1007/s00134-011-2452-5
|View full text |Cite
|
Sign up to set email alerts
|

In-line filter included into the syringe infusion pump assembly reduces flow irregularities

Abstract: In the evaluated model in-line filters help to reduce flow irregularities and delay in drug delivery of syringe pumps at low flow rates and represent an option to optimize continuous administration of highly concentrated short-acting drugs at very small infusion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Table 4 summarises the data from recent clinical studies assessing the clinical impact of in-line filters. In addition to reducing flow rate irregularities and start-up times at low infusion rates [24], the placing of an in-line infusion filter has no adverse effect on in-line pressure monitoring [26]. However, there is insufficient evidence to recommend the use of intravenous in-line filters to prevent morbidity or mortality in neonates [27] although it is recommended when administering parenteral nutrition solutions, specifically in European guidelines for paediatrics [94].…”
Section: Prevention Of Drug Incompatibilitiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Table 4 summarises the data from recent clinical studies assessing the clinical impact of in-line filters. In addition to reducing flow rate irregularities and start-up times at low infusion rates [24], the placing of an in-line infusion filter has no adverse effect on in-line pressure monitoring [26]. However, there is insufficient evidence to recommend the use of intravenous in-line filters to prevent morbidity or mortality in neonates [27] although it is recommended when administering parenteral nutrition solutions, specifically in European guidelines for paediatrics [94].…”
Section: Prevention Of Drug Incompatibilitiesmentioning
confidence: 97%
“…An in-line filter is used to avoid administering non-visible particles to the patient, including those resulting from drug incompatibilities and materials, especially common and serious in paediatrics and neonatology [24,66,67]. The impact of in-line filters on infusion rate has been evoked for one model drug [57] and was assessed in a study that showed that their use reduced flow rate irregularities and start-up times at low infusion rates [24].…”
Section: In-line Filtersmentioning
confidence: 98%
See 2 more Smart Citations
“…Not all drugs are filterable, such as suspensions, micellar solutions, liposomes, having a high viscosity or a risk of adsorption on the filter membrane. In addition, a recent study showed that the presence of an in-line filter on the infusion line reduced flow irregularities, as well as the start-up time of the syringe pumps at low flow rates [25].…”
Section: Factorsmentioning
confidence: 99%